Peningkatan Produktivitas Produk Kerang Hijau di Usaha Mikro Kecil Berkah Mandiri Desa Banyuurip Kabupaten Gresik - Nurdiani, Rahmi; Prihanto, Asep Awaludin; Chawa, Anif Fatwa; Kusuma, Titis Sari; Perdana, Angga Wira (Jurnal Pemberdayaan Masyarakat, 2023)
Banyuurip Village has considerable aquaculture potential, one of which is the culture of green mussels. Abundant production and its low price encourage people to do green mussel products processing. In 2019, UMKM Berkah Mandiri was established to increase the selling value of green mussels by innovating several products. However, the production process is still experiencing ups and downs, coupled with inadequate equipment. In addition, the distribution permit (SPP-PIRT) for the products have not been obtained. Therefore, the aim of the Doctoral community service program was to increase the productivity of UMKM Berkah Mandiri through a series of marketing strategy training activities, registration of NIB and SPP-PIRT and procurement of new production and packaging equipment. At the end of the Doctoral community service program, UMKM Berkah Mandiri has successfully obtained the SPP-IRT certificate and has better understanding of good manufacturing practice of products from green mussels. In addition, the crackers have been tested its nutritional content using a proximate test. The results showed that the protein, moisture, fat, ash and carbohydrate contents of Kopang cracker was 5.30%, 13.83%, 0.69%, 2.99% and 77.19%, respectively. The nutritional content list is used to improve product packaging in accordance with BPOM packaging standards.